What jurist dont say. Unexpressed and de-positivating norms - Barberis, Mauro (2019)
One of the most intriguing issues treated by recent legal theory are implicit and/or unexpressed norms. However, this topic, proposed by Riccardo Guastini in the last century’s Nineties, evidently embarrasses other lawyers and law theorists; in fact, it is discussed almost by Genoeses and their friends alone, as we shall see. The paper reconstructs the thematization of this problem, deeply connected with other typical «Genoese» topics such as interpretation / construction distinction and the very concept of Kelsenian Rahmen. Finally, a distinction of implicit and (totally) unexpressed norms is proposed, by redefining implicit ones as a dependent variable of judicial application and dealing with unexpressed norms as an element of a process I call law’s de-positivization.